Western Tarsier Cephalopachus bancanus at Matang Wildlife Centre, Sarawak - Nur Mukminah, Naharuddin; Faisal Ali, Anwarali Khan; Mohd Ridwan, Abd Rahman (Ecologyasia, 2017)
The huge, forward-facing eyes, large ears and small body size immediately identify this animal as a tarsier. The Western Tarsier Cephalopachus bancanus is the only species currently recognized on the island of Borneo: it mainly inhabits lowland areas, but there are montane records up to 1200 metres elevation.